Sustainable Ceramic Membranes from Clays and Mining Wastes by Rapid Sintering Process - Hellen C. T. Firmino; Déborah dos S. Gomes; Vanderlane C. da Silva; Ieda M. G. Santos; Helio L. Lira; Lisiane N. L. Santana; Romualdo R. Menezes; Gelmires de A. Neves (Materials Research)
This study characterized wastes from scheelite and columbite-tantalite mining, as well as kaolin processing, to produce microfiltration membranes for wastewater treatment using a fast-sintered process. After characterization, the wastes were mixed with clays, pressed, and sintered at low temperatures of 1050 and 1100 °C. The resulting membranes exhibited pore size distributions ranging from 3 μm to 180 μm and flexural strengths exceeding 14 MPa. In a crossflow filtration system, permeate fluxes ranged from 177 L/h.m2 to 228 L/h.m2 at 2 bar, with permeabilities from 99 to 130 L/h.m2 bar depending on the waste content. Membranes with smaller pore sizes effectively removed 90% to 96% of turbidity from a water/clay suspension containing micrometric clay particles. This approach demonstrates that rapid sintering of ceramic membranes from mining waste can effectively reduce environmental impacts and energy costs, providing a sustainable solution for wastewater treatment.